1996
DOI: 10.1002/j.1460-2075.1996.tb00936.x
|View full text |Cite
|
Sign up to set email alerts
|

Single point mutations in various domains of a plant plasma membrane H(+)-ATPase expressed in Saccharomyces cerevisiae increase H(+)-pumping and permit yeast growth at low pH.

Abstract: In plants, the proton pump‐ATPase (H(+)‐ATPase) of the plasma membrane is encoded by a multigene family. The PMA2 (plasma membrane H(+)‐ATPase) isoform from Nicotiana plumbaginifolia was previously shown to be capable of functionally replacing the yeast H(+)‐ATPase, provided that the external pH was kept above pH 5.5. In this study, we used a positive selection to isolate 19 single point mutations of PMA2 which permit the growth of yeast cells at pH 4.0. Thirteen mutations were restricted to the C‐terminus reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
113
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(130 citation statements)
references
References 64 publications
(54 reference statements)
11
113
1
1
Order By: Relevance
“…Glucose dependent H ϩ extrusion from yeast cells was measured essentially as reported in Morsomme et al (1996). The cell suspension was stabilized at pH 5.5 by titration with NaOH and HCl before starting the assay.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Glucose dependent H ϩ extrusion from yeast cells was measured essentially as reported in Morsomme et al (1996). The cell suspension was stabilized at pH 5.5 by titration with NaOH and HCl before starting the assay.…”
Section: Methodsmentioning
confidence: 99%
“…The acidification of the external medium by yeast cells can be used as a measure for the activity of H ϩ -ATPase in the plasma membrane (Baunsgaard et al, 1996;Morsomme et al, 1996). When glucose was added to the medium as a carbon source the cells responded by extruding H ϩ (Figure 1b).…”
Section: Fusicoccin Activates H ϩ Extrusion From Yeast Cells Expressimentioning
confidence: 99%
See 1 more Smart Citation
“…The H ϩ -ATPase activity is thought to be regulated by an autoinhibitory domain in the C-terminal region of the enzyme. Removal of a 7-10 kDa fragment from the C-terminal end of H ϩ -ATPase generates a high-activity state of H ϩ -ATPase with a higher V max , a lower K m for ATP, a changed pH dependence with higher activity at physiological pH and an increased coupling of H ϩ transport with ATP hydrolysis (Palmgren et al, 1990;Morsomme et al, 1996;Sze et al, 1999). Very similar results were obtained by in vivo treatment of intact tissue with the fungal toxin fusicoccin (FC), an activator of the H ϩ -ATPase, and it is suggested that FC induces a displacement of the C-terminal autoinhibitory domain of H ϩ -ATPase from its catalytic site (Palmgren, 1991;Johansson et al, 1993;Rasi-Caldogno et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…ATP hydrolysis is sufficient to account for the observed H ϩ pumping, since the enzyme is assumed to have a stoichiometry of 2H ϩ / ATP (Spanswick, 1981) or H ϩ /ATP (Briskin and ReynoldsNiesman, 1991). It is also possible that BL concomitantly improves the coupling between H ϩ pumping and ATP hydrolysis (Baunsgaard et al, 1996;Morsomme et al, 1996). (A) BL-dependent H ϩ pumping in GCPs was measured by the decrease of pH in the medium.…”
Section: Introductionmentioning
confidence: 99%